Implementation of Family Counseling at the Family Service Center (PUSPAGA) and UPTD PPA: Efforts to Improve Family Resilience in Kendari City - Khairunnisa Syamsu (Universitas PGRI SUMATERA BARAT, 2025)
The family, as the smallest social unit, plays a critical role in shaping individuals’ personality, values, and social competence, yet modern challenges such as marital conflict, communication breakdowns, and socio-economic pressures often disrupt household harmony. Family counseling services are thus essential to strengthen resilience and provide solutions to complex problems. This study examines the implementation of family counseling services at the Family Learning Center (PUSPAGA) and the Regional Technical Implementation Unit for the Protection of Women and Children (UPTD PPA) under the Department of Women’s Empowerment and Child Protection (DP3A) in Kendari City. Using a qualitative descriptive design, data were collected through observation, interviews, and documentation involving counselors and clients, and analyzed with Miles and Huberman’s interactive model, supported by triangulation to ensure credibility. The findings indicate that PUSPAGA provides structured services through registration, assessment, consultation, family visits, counseling, and referrals, supported by techniques such as attending, empathy, reflection, exploration, and questioning strategies. The theoretical foundations applied include Rational Emotive Behavior Therapy (REBT), which helps clients replace irrational with rational thoughts, and Adlerian theory, which emphasizes social interest and lifestyle modification. While PUSPAGA combines counseling with family education, UPTD PPA focuses on initial assessment and referral of severe cases such as domestic violence and sexual abuse to psychologists or legal authorities. The study concludes that both institutions complement each other in addressing family problems and recommends continuous counselor training, stronger collaboration with professional and legal stakeholders, the use of digital platforms to expand access, and the development of structured SOPs to enhance service consistency and impact.